Intestinal vitamin D receptor protects against extraintestinal breast cancer tumorigenesis. (31st December 2023) - Zhang, Yong-Guo; Xia, Yinglin; Zhang, Jilei; Deb, Shreya; Garrett, Shari; Sun, Jun
ABSTRACT: The microbiota plays critical roles in regulating the function and health of the intestine and extraintestinal organs. A fundamental question is whether an intestinal-microbiome-breast axis exists during the development of breast cancer. If so, what are the roles of host factors? Vitamin D receptor (VDR) involves host factors and the human microbiome. Vdr gene variation shapes the human microbiome, and VDR deficiency leads to dysbiosis. We hypothesized that intestinal VDR protects hosts against tumorigenesis in the breast. We examined a 7, 12-dimethylbenzanthracene (DMBA)-induced breast cancer model in intestinal epithelial VDR knockout (VDR ΔIEC ) mice with dysbiosis. We reported that VDR ΔIEC mice with dysbiosis are more susceptible to breast cancer induced by DMBA. Intestinal and breast microbiota analysis showed that VDR deficiency leads to a bacterial profile shift from normal to susceptible to carcinogenesis. We found enhanced bacterial staining within breast tumors. At the molecular and cellular levels, we identified the mechanisms by which intestinal epithelial VDR deficiency led to increased gut permeability, disrupted tight junctions, microbial translocation, and enhanced inflammation, thus increasing tumor size and number in the breast. Furthermore, treatment with the beneficial bacterial metabolite butyrate or the probiotic Lactobacillus plantarum reduced breast tumors, enhanced tight junctions, inhibited inflammation, increased butyryl-CoA transferase, and decreased levels of breast Streptococcus bacteria in VDR ΔIEC mice. The gut microbiome contributes to the pathogenesis of diseases not only in the intestine but also in the breast. Our study provides insights into the mechanism by which intestinal VDR dysfunction and gut dysbiosis lead to a high risk of extraintestinal tumorigenesis. Gut-tumor-microbiome interactions represent a new target in the prevention and treatment of breast cancer.